Total hip arthroplasty in elderly patients: treatment-specific considerations, risk of complications, and functional outcomes - Halik, Paulina; Jusiak , Justyna; Grabińska, Magdalena; Kubala , Karolina; Gołdyn , Mikołaj; Pietrucha, Tomasz; Stupnicki, Szymon (Quality in Sport, 2026)
Introduction Total hip arthroplasty (THA) is a widely used and effective procedure for treating advanced hip disorders. With population aging, the number of THA procedures in elderly patients is steadily increasing. Advanced age is associated with comorbidities and reduced physiological reserve, which may influence perioperative risk and postoperative outcomes. Aim This review aimed to summarize current evidence on total hip arthroplasty in elderly patients, focusing on surgical management, perioperative care, rehabilitation, and clinical outcomes. Materials and methods A narrative review of the literature was conducted using PubMed, Scopus, and Web of Science databases. Publications between 2001 and 2025 were included. The review focused on adults aged ≥65 years and synthesized findings narratively across surgical indications and management, perioperative care, risk of complications, rehabilitation, and functional outcomes following total hip arthroplasty. Results Available evidence indicates that THA provides significant pain relief and functional improvement in elderly patients, including those aged 80 years and older. Cemented implants are associated with lower early revision rates and better implant survival in patients with poor bone quality, while uncemented and hybrid prostheses may be appropriate in selected cases. Elderly patients have a higher risk of perioperative complications, such as cardiopulmonary events, delirium, and periprosthetic fractures. Early mobilization and structured rehabilitation significantly improve functional recovery and reduce complication rates. Conclusion Total hip arthroplasty is a safe and effective treatment option for elderly patients when individualized surgical planning, comprehensive perioperative management, and multidisciplinary rehabilitation are applied. Advanced age alone should not be considered a contraindication to surgery.